2014
DOI: 10.1002/2014ja020522
|View full text |Cite
|
Sign up to set email alerts
|

Event study combining magnetospheric and ionospheric perspectives of the substorm current wedge modeling

Abstract: Key Points:• Azimuthal SCW dynamics nicely order various substorm signatures in the tail • AMPERE confirms quadrupolar FAC source of SCW supporting two-loop model • SCW2L model outperforms other models in describing dipolarized configuration Supporting Information:• Readme • Animation S1• Animation S2• Figure S1 • Figure S2 • Figure S3 Correspondence to: Abstract Unprecedented spacecraft and instrumental coverage and the isolated nature and distinct step-like development of a substorm on 17 March 2010 has allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 27 publications
(58 reference statements)
3
17
0
Order By: Relevance
“…Both sets of observations are consistent with the expanding/contracting polar cap (ECPC) model of the Dungey cycle of magnetospheric and ionospheric convection [Dungey, 1961;Siscoe and Huang, 1985;Cowley and Lockwood, 1992;Lockwood and Cowley, 1992;Milan et al, 2007;Milan, 2015]. In addition, Murphy et al [2013] and Sergeev et al [2014] have used AMPERE observations to explore the structure of nightside FACs during substorms, specifically attempting to elucidate the structure of the substorm current wedge [McPherron et al, 1973], while Wilder et al [2013] studied cusp currents associated with magnetic tension forces during periods of nonzero IMF B Y .…”
Section: Introductionsupporting
confidence: 75%
“…Both sets of observations are consistent with the expanding/contracting polar cap (ECPC) model of the Dungey cycle of magnetospheric and ionospheric convection [Dungey, 1961;Siscoe and Huang, 1985;Cowley and Lockwood, 1992;Lockwood and Cowley, 1992;Milan et al, 2007;Milan, 2015]. In addition, Murphy et al [2013] and Sergeev et al [2014] have used AMPERE observations to explore the structure of nightside FACs during substorms, specifically attempting to elucidate the structure of the substorm current wedge [McPherron et al, 1973], while Wilder et al [2013] studied cusp currents associated with magnetic tension forces during periods of nonzero IMF B Y .…”
Section: Introductionsupporting
confidence: 75%
“…Thirdly, substorms are associated with the formation of the substorm current wedge (SCW) with additional field-aligned currents diverting current from the magnetotail into the nightside ionosphere. Clausen et al (2013a) showed that on average the formation of the SCW enhances the nightside portions of the region 1 current system, though it is also known that the substorm FACs can be highly filamentary (e.g., Forsyth et al 2014), on spatial scales much finer than can be resolved with AMPERE, and evolve with time during the expansion phase (e.g., Sergeev et al 2014). Indeed, we found no clear signature of a SCW in the substorm presented in Fig.…”
Section: Substormsmentioning
confidence: 54%
“…Data from AMPERE have provided new insights into the dynamics of the global FACs during substorms (see recent review by Coxon et al, ). As expected, the FACs increase after substorm onset (Clausen, Milan, et al, ; Clausen et al, ; Sergeev et al, ; Sergeev et al, ), with substorms at lower latitudes generally being associated with larger FACs (Coxon et al, ). Furthermore, the Region 1 and Region 2 current systems move in conjunction with the opening and closing of magnetic flux, determined using the location of the R 1 current system as a proxy for the open‐closed field line boundary (Clausen et al, , , ).…”
Section: Introductionmentioning
confidence: 60%
“…This forms a new FAC system (Akasofu & Chapman, ; Mcpherron et al, ) or enhances the magnitude of and moves existing FACs (Friedrich & Rostoker, ; Rostoker, ; Rostoker & Friedrich, ). Recent studies have suggested that the substorm current wedge could also include a R 2 ‐type current system (Coxon et al, ; Liu et al, ; Ritter & Luhr, ; Sergeev et al, ). Some 15–30 min after the substorm onset, the currents begin to reduce toward their presubstorm levels in a period known as the recovery phase.…”
Section: Introductionmentioning
confidence: 99%